US Turn to Protectionism : How Should Asia Respond? - Kikuchi, Tomoo (2018)
The US turns to protectionism as it becomes less dependent on oil from the Middle East, aiming to reduce its government debt and revitalise its manufacturing industries. The world needs to step up to create a new inclusive economic and security order.